Defining criterias of Shariah compliant hotel rooms - Saifuddin, Syaza; Othman, Rashidi; Md Hashim, Muhammad Hafizuddin Akmal; Jasmani, Ismail; Abdul Majid, Noor Hanita (2016)
This paper defines criteria of various sampling locations used to test out the criteria of what a Fully Shariah Compliant Hotel Room should be. This paper reviews the theoretical views in establishing a suitable and optimum environment for Muslim in a supposedly fully shariah compliant environment. It involves a few research methodologies that requires the researcher to study on a few characteristics needed to test out whether the proper criteria's are applied to ensure that the awarded fully shariah compliant hotel rooms comply to the needs of Muslim guests. This paper intends on revealing the elements that are vital and may contribute for hotels in achieving a more conclusive research on space planning for hotel rooms focusing on the shariah and Muslim guests.